(3TQM OjhGf CHj aQGSs - (3YHO GddWja Hf HgGA GdOjf GdTGejs; (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s ((3WQGHdS s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdGfSGf hLYd Yde GdGOH hSjdI Edi age CSQGQ GdHdGZI GdLjdI GdTCf s
(3BNQgG (B:s
(3hdYd gPG GdHjJ JdejM Edi bhdg (B: (3Udi Gddg Ydjg hSde (B( (3hLYd QRbi JMJ Xd QeMi (B) (3hGdMeO ddg Ydi cd MGd aGf gPG BNQ TYQ bGdg CHh aQGS QMeg Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B488s
Keywords: (3GdCOHs